TINDAK LANJUT HASIL AUDIT DAN TRANSPARANSI, PENGARUHNYA TERHADAP TINGKAT KORUPSI DI INDONESIA : FOLLOW-UP ON AUDIT RESULTS AND TRANSPARENCY, ITS INFLUENCE ON THE LEVEL OF CORRUPTION IN INDONESIA - Aprillia, Dhea; Periansya, Periansya; Aryani, Yuli Antina (Universitas Riau, 2025)
A case study of corruption cases handled by the Corruption Eradication Commission in 2018–2022 seeks to determine the impact of transparency on the level of corruption and the effects of follow-up activities on audit results. Secondary data for this study came from sources such as the KPK Financial Report, provincial government websites, and the BPK RI Audit Result Report and Summary of Semester II Audit Results. This study covers the 2018–2022 fiscal years, using 33 research samples and focusing on 34 provinces in Indonesia. Using SPSS version 25, we conducted multiple linear regression analyses to test the hypotheses. According to the study findings, transparency and follow-up on audit findings both have a positive and substantial effect on the level of corruption. At the same time, openness and the amount of time spent following up on audit findings affect the prevalence of corruption